The Future Perfect of Suspicion and Prediction as a Dispositive of Security Today? The Legacy of Foucault (1977). - BIGO, DIDIER (Foucault Studies, 2024)
This article discusses the current legacy of Michel Foucault in relation to the current political situation. It is articulated in three parts. The first insists on the fact that Michel Foucault has been and still is significant for discussions concerning political sciences and international relations by the way he has discussed them and by his own academic politics. The second part highlights the key role of his attempt to define a dispositif of security in the 1977-78 lecture course 'Security, Territory, Population' and the various interpretations given after his death. The third part introduces my own research on the subject and its development. Twenty years ago, I called this dispositif of security surveillance a ban-opticon dispositif. This is only partly relevant since the violence of the effects on individuals has been intensified by a multifocal construction of "suspects" by various transnational guilds of security professionals who systematise profiling and weak correlations as an alternative method of seeking the truth about causalities and facts attributed to an individual. Because of this systematicity of "suspicion first", which jeopardises the principle of innocence, I call this dispositif of security a transnational dispositif of suspicion-prediction, which is organised both as a rearticulation of the modern episteme with suspicion back at its core and as a "legitimate" one, thus allowing a "preventive" violence to be re-enacted in the name of scientific predictions of a future so deadly that it is necessary to act violently now in order to prevent even more violence. This question of inverted temporality, in which the imagined future dominates the present, leads to the belief that the future can already be known under a grammar of the future perfect. Combined with the strategic orientation of right-wing parties to abandon the celebration of the past in order to mobilise the fear of apocalyptic futures, this characteristic of the 'future-perfect' explains a series of contemporary developments in security and surveillance, reframing the attachment of the population to a new form of conservatism that captures the imagination of the future, including some contemporary discourses of war. Resisting this attraction to the future-perfect is possible by reinventing hope.